Cost-benefit analysis of surgical appendectomy in the brazilian public health system (Research, Society and Development, 2022)
Objectives: To compare the number of hospitalized patients, the number of deaths, days of hospitalization, and values of hospital services with open appendectomy and video-laparoscopic appendectomy procedures. To compare the cost-benefit of open appendectomy and video-laparoscopic appendectomy procedures. To compare the effectiveness of open appendectomy and video-laparoscopic appendectomy procedures. Methodology: This research was carried out through a retrospective, quantitative study, with temporal secondary data collected from the DATASUS database. Scientific articles collected on the electronic data platform Scientific Electronic Library Online (SCIELO), US National Library of Medicine (PubMed), and the Ministry of Health (MS) were used to discuss the results. Results: The number of open appendectomies increased by 130.86% from 2008 to 2018, while the number of video-laparoscopic appendectomies increased by 708.31%. The most developed Brazilian regions, that is, South and Southeast, totaled more than half of all laparoscopic procedures performed in Brazil, adding up to 85.52% of the total value. The death rate was 0.27% in open appendectomy and 0.09% in video-laparoscopic appendectomy. Therefore, the death rate was 66.7% lower in video-laparoscopic appendectomy. The average cost to the public coffers was 383.02 Reais for each open appendectomy and 403.02 Reais for each closed appendectomy. Conclusion: The analysis of the unknowns related to appendicitis surgeries shows that factors such as deaths, the average length of stay, and the value of hospital services have significant differences for the doctor and the patient.